Aspects of reproductive biology of Mediterranean amberjack (Seriola dumerilii Risso, 1810): Gonadal development - Marino G.; Porrello S.; Andaloro F.; Massari A.; Mandich A. (Marine aquaculture finfish species diversification, 1995)
Wild Seriola dumerilii juveniles (77.3 plus minus 23 g total body weight, 17.4 plus minus 1.8 cm standard length; 2-3 months of age), were caught in the Eolian Island and reared in floating cages for a 14 months period. Gonads were collected routineously and submitted to histological and histochemical analysis to study the type and timing of gonadal differentiation and development. The histological examination shows that sex differentiation is clearly expressed in juveniles 23-25.5 cm long, 4-5 months old. A 'differenciated' development was detected, as sexes early differenciate into female or male. In both sexes, anatomical and cytological differentiation proceed in parallel. Gonadal differentiation is completely achieved by the end of the first year of age. Within this period also cytological differentiation was completed in reared males, whereas females do not show the secondary growth phase oocytes. These findings agree with the previous data on wild S. dumerilii caught in natural environments. Comparing data reported by other authors, gonadal development seems to be linked to fish size more than to age. Gonadal development in cage-reared fish was continuous and no pathological or degenerative signs were histologically observed. From an aquaculture perspective, cage rearing conditions, being similar to the natural ones, seem to be suitable to correctly develop and manage broodstock in captivity.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1995/06/14-17, Nicosia (Cyprus)